SELEKSI BAKTERI ASAM LAKTAT PENGHASIL AMILASE DAN PULULANASE DAN APLIKASINYA PADA FERMENTASI TALAS - R. Haryo Bimo Setiarto; Betty Sri Laksmi Jenie; Didah Nur Faridah; Iwan Saskiawan; Sulistiani - (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2015)
The objective of this study were to select amylase and pululanase producing lactic acid bacteria (LAB) for taro fermentation and to find out the length of fermentation time that will produce short chain polysaccharide. Fourty one LAB isolates were selected based on the amylase and pululanase activity (U/mL). Three isolates of LAB i.e. Lactobacillus plantarum D-240, SU-LS67 and SU-LS59 demonstrated the highest enzyme activities among other strains. The amylase activity for those three isolates was 2.57, 2.70, and 2.50 U/mL, respectively and the pullulanase activity was 2.72, 2.88 and 2.91 U/mL, respectively. Genotypic identification was conducted for strains SU-LS59 and SU-LS67. Strains identification by sequencing the gene encoding 16S rDNA and phylogenetic analysis using Neighbor Joining method showed that both isolates were identical to Leuconostoc mesenteroides NBRC 100496T (AB681194 ) with a bootstrap value of 100%. Either single or mixed culture of L. plantarum D-240 and L. mesenteroides SU-LS 67 were then used as starter in taro fermentation and DP values of the taro starch were examined at various fermentation times (0, 6, 12, 18, 24 h). The results showed that applying 2% mixed culture (108 CFU/mL) of L. plantarum D-240 and L. mesenteroides SU-LS 67) at the ratio of 1:1 as starter in taro fermentation was found more effective than the single cultures due to its ability to hydrolize and generate starch with DP value around 27 after 18 h fermentation. Starch with DP values between 19-29 was considered suitable for the formation of resistant starch (RS) during autoclaving-cooling cycles. This finding might be advantageous as preliminary treatment for the production of RS-rich taro flour through autoclaving-cooling process.